Antihyperglycemic and analgesic activity studies with Bambusa spinosa aerial parts - Naieeam M Adnan, Rahat Al-Mahamud, Anuj Kumer Das, Shahnaz Rahman, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
Bambusa spinosa (Poaceae) is a common type of bamboo found in Bangladesh where it is known as Kata bash. It was of interest to evaluate the antihyperglycemic and analgesic potential of its aerial parts as part of our antihyperglycemic and analgesic plant screening program. In oral glucose tolerance tests, methanol extract of aerial parts of the plant (MEBS) significantly and dose-dependently reduced blood glucose levels in glucose-loaded mice by 37.5, 52.8, 58.3, and 66.8%, respectively, at doses of 50, 100, 200 and 400 mg per kg in comparison to a standard antihyperglycemic drug, glibenclamide, which reduced blood glucose levels by 60.7% at a dose of 10 mg per kg. In acetic acid induced writhing tests in mice, MEBS at the afore-mentioned doses significantly reduced the number of writhings, respectively, by 23.3, 36.7, 46.7, and 60.0% versus the 40.0 and 46.7% reductions observed with a standard analgesic drug, aspirin, at doses of 200 and 400 mg per kg, respectively. MEBS thus demonstrated considerable antihyperglycemic and analgesic properties and may be considered for use to alleviate high blood sugar levels and pain.
Keywords: Analgesic,Bambusa spinosa,antihyperglycemic,Poaceae.